IKHTILAF MADZHAB FIQIH DALAM NIAT SEBULAN PENUH PUASA RAMADHAN - Multazim Ali Ahmadi (VICRATINA, 2019)
The ulama of the four schools agreed that the fast of Ramadan must begin with intention. It's just that they disagree about the technical intentions. According to three schools other than Malikiyyah, it is mandatory to repeat the intention every time fasting. This study aims to find out the law of fasting intention and intention of one month of Ramadan fasting in one intention. The method used in this study uses a library research method, library research or literature can be interpreted as a series of activities relating to the method of collecting library data, reading and recording and processing research material. and the results of this study are as follows: 1) the intention in legal fasting is to be carried out. And this was agreed upon by the four schools of jurisprudence including Hanafi, Maliki, Syafii and Hanbali. 2) Hanafi, Syafii and Hanbali schools agree that the intention of fasting must be carried out every day so that the intention of not fasting is immediately permitted for a full month. But the Maliki school of thought allowed this because it was argued that the fasting of Ramadan must be carried out continuously, so that the law is the same as one worship. And one worship only requires one intention.Keywords:madzhab fiqih, ramadhan